Концепт «differаnce» в философии Ж. Деррида - Азарова, Ю.О. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2010)
Статья содержит анализ понятия differаnce, выполняющего главную роль в проекте деконструкции метафизики Жака Деррида; раскрывает базовые значения и функции differаnce; определяет специфику работы differаnce в философском дискурсе; демонстрирует эвристические возможности differаnce в создании нового неклассического типа рациональности. Стаття містить аналіз поняття differаnce, яке виконує провідну роль в деконструкції метафізики Жака Дерріда; висвітлює головні значення та функції differаnce; розкриває специфіку роботи differаnce в філософському дискурсі; визначає евристичні можливості differаnce в створенні нового некласичного типу раціональності. This issue contains the analysis differаnce that has decisive importance in Jacques Derrida’s deconstruction of metaphysics. The author searches are main meanings and function of differаnce, demonstrates specific work of differаnce in philosophical discourse, and exposes cognition possibilities of differаnce for new post-classic rationality.
Keywords: differаnce; time; spaсe; ontic-ontological difference; differаnce; время; пространство; онтико-онтологическое различие